Digital Parenting and Children’s Creativity among Dharma Wanita Persatuan BBIB Members - Amaliah Ekasari; Pujiyanti Fauziah; Yudan Hermawan (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study aims to analyse the use of technology in the parenting patterns of members of the Dharma Wanita Persatuan (DWP) Balai Besar Inseminasi Buatan (BBIB) Ministry of Agriculture in developing children's creativity. Using a qualitative approach with a case study design, this study involved ten mothers who are members of the DWP BBIB who have children aged 5–12 years. Data were obtained through in-depth interviews, participatory observation, and documentation, then analysed using the Miles, Huberman, and Saldaña (2018) model. The results showed that technology was used not only as a means of entertainment but also as an educational and creative medium through activities such as digital drawing, making educational videos, and project-based experiments. The mothers acted as idea facilitators, moral mediators, and time and content controllers, creating an authoritative parenting environment that balanced freedom of exploration and discipline. Reflective use of technology strengthens emotional bonds, enhances critical thinking skills, and fosters children's creative expression. This study confirms that intelligent digital parenting based on cultural and spiritual values can shape a creative generation that is adaptable to technological change.